KEPAILITAN DEBITUR DALAM PRAKTIK PERADILAN - Tami Rusli (Universitas Bandar Lampung (UBL), 2019)
Bankruptcy law is very dominant in protecting the interests of creditors, it can be seenfrom the requirements that must be declared bankrupt namely the existence of two or moredebts, and one of them has matured. Bankruptcy to the Debtor can be granted if the Debtor isno longer able to pay its debts. The problem in this study is how the position of the debtor inbankruptcy in judicial practice. The method used by the normative juridical approach andanalysis is carried out qualitatively. The results showed that the application for bankruptcystatements in both the applicant and respondent's petition was individual, the Court did notconsider the position of the Petitioner or Respondent, the Court only considered the extent ofthe legal relationship that exists between the Petitioner and the Petitioner. and theRespondent in this bankruptcy request. The court considers whether the request for abankruptcy statement is in accordance with the provisions stated in Article 2 paragraph (1)of the Bankruptcy Act, and whether the evidence is simple, the Court is of the opinion that allrequirements are fulfilled